Levantamiento, definición y formalización de los procesos de seguridad de la información en la unidad de telecomunicaciones e información de la Universidad Nacional de Loja. - Cuenca Capa, Maritza Lorena (2017)
At present, one of the most important assets for any kind of institution is information, therefore, information management is paramount to preserve confidentiality, integrity and availability, which must be protection to ensure the features. The approach of the present research seeks to manage the protection of information assets of property of Universidad Nacional de Loja, managed by the Telecommunications and Information Unit. This investigation deals with the gathering, definition and formalization of information security processes inside the Telecommunications and Information Unit of Universidad Nacional de Loja, ISO / IEC 27002: 2013 standard is used as a reference framework, using the SIPOC methodology (Suppliers, Inputs, Process, Outputs, Customers) to define and manage the processes, allowing the PDCA (Plan-Do-Check-Act) cycle to be applied continuously within regulations. Finally, e information security processes were formalized with the Unit officials, the director and the information security administrator of the Telecommunications and Information Unit.